The Russian to non-Russian Speaker Wage Gap in The Banking Sector of Azerbaijan - Hajili, Narmin; Guluzada, Shahin; Guliyev, Ramil; Mammadov, Fuad; Zulfuzada, Ismayil (ADA University, 2019)
Authority of Soviet Union in Azerbaijan in the 20th century is well known by the world. Its impacts are still feeling in the society of modern Azerbaijan. The research focuses one of these impacts which is discrimination towards workers who do not know Russian language. The data was conducted from workers in banking sector by distributing survey. The main reason of choosing banking sector is its homogeneity and similarity of requirements from workers. Under these circumstances general situation of workers become more equal and it helps inequalities to be felt easily. If there is any discrimination in labor market it can lead polarization of society in the future. Therefore, the result of paper can be useful for policymakers in order to avoid problems in the society.
Keywords: Business; Banking sector; Language discrimination; Wage--Azerbaijan; Labor market--Azerbaijan